Evaluation of nasal airway patency by analysis of breathing sounds. (1st February 2016) - Primov-Fever, Adi; Zaretsky, Uri; Elad, David; Wolf, Michael
Abstract: Conclusions : A simple non-invasive method, based on acoustic analysis of breathing signals, revealed a potential for objective evaluation of differences between the patency of nasal passageways. Objectives : To examine whether acoustic signals of nasal breathing contain information that can differentiate between obstructed and patent nasal passageways. Method : A technical study aimed to examine measurements of nasal airflow acoustic signals, taken, non-invasively, simultaneously from both external sides of the nostrils. The signals were acquired for several breathing cycles, with different respiratory efforts, before and after application of a nasal decongestant to the (narrower) side that yielded lower amplitudes. Data processing of the expiratory phase yielded the power spectrum density (PSD), which was used to compute the ratio of PSD areas between the signals from both sides of the nose. The study group was composed of 20 healthy volunteers. Results : PSD changes were noted in accordance with the rise in expiratory efforts. The ratio of PSD areas between the two sides of the nasal cavity, calculated for maximal expiratory efforts, correlated well with the side that was treated with nasal decongestant in 18 out of the 20. Changes in the opposite direction were noted in two examinees.